2023
DOI: 10.2174/1570159x20666220327213615
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline and Seizures: A Perspective on the Role of Adrenergic Receptors in Limbic Seizures

Abstract: Background: Noradrenergic fibers originating from the locus coeruleus densely innervate limbic structures including the piriform cortex, which is the limbic structure with the lowest seizure threshold. Noradrenaline (NA) modulates limbic seizures, while stimulating autophagy through β2-adrenergic receptors (AR). Since autophagy is related to seizure threshold, this perspective questions whether modulating β2-AR focally within the anterior piriform cortex, affects limbic seizures. Objective: In this perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Norepinephrine exerts its anticonvulsant effects through β2-adrenergic receptors by stimulating the autophagy pathway. Noradrenergic fibers originating from the locus coeruleus densely innervate limbic structures, including the piriform cortex, which represents the limbic structure with the lowest seizure threshold [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Norepinephrine exerts its anticonvulsant effects through β2-adrenergic receptors by stimulating the autophagy pathway. Noradrenergic fibers originating from the locus coeruleus densely innervate limbic structures, including the piriform cortex, which represents the limbic structure with the lowest seizure threshold [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plasticityinducing effects of LC are extended to a variety of physiological and pathological conditions (Fornai et al, 2011;Galgani et al, 2020;Gesi et al, 2000;Giorgi et al, 2003;Giorgi et al, 2006;Giorgi et al, 2008;Giorgi et al, 2017;Giorgi et al, 2019;Giorgi et al, 2020a;Giorgi et al, 2020b;Giorgi et al, 2021a;Giorgi et al, 2021b;Giorgi et al, 2022;Ruffoli et al, 2011), which include learning and memory and seizures. In all these cases a prominent role is exerted by beta receptors, which modulate specific intracellular signaling pathways (Lazzeri et al, 2021;Biagioni et al, 2022). The role of LC in photic plasticity emerged in the study by Watabe et al, (1982), who showed activation of the reticular nucleus LC following the stimulation of both geniculate and extra-geniculate pathways including: the optic chiasm (OX), the dorsal lateral geniculate nucleus (LGN), the superior colliculus (SC), and the visual cortex (VC).…”
Section: The Effects Of Light Exposure On Plasticity Of Vegetative An...mentioning
confidence: 99%
“…In particular, NE axons arising from LC (LC-NE) protect against neuronal damage in a variety of degenerative disorders [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. This evidence encompasses acute neurological insults, such as epileptic seizures [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], brain ischemia [ 34 , 35 , 36 ], and chronic degenerative disorders. In fact, the protective effects of LC are mostly evident at disease onset and during the course of chronic neurodegeneration, such as experimental Parkinsonism induced in rodents [ 37 , 38 , 39 ] and monkeys [ 40 ], as well as in persons affected by Parkinson’s disease (PD) [ 12 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%